Pengaruh Hadiah dalam Kemasan, Kualitas Produk, dan Distribusi Produk terhadap Keputusan Pembelian TosTos : (Studi Kasus pada Penggemar NCT Dream di Bekasi Utara) - Safira Krisnanintias; Andrian Andrian; Haryudi Anas (Universitas Kristen Indonesia Toraja, 2024)
This research aims to empirically test the influence of gifts in packaging, product quality, and product distribution on TosTos purchasing decisions (case study of NCT Dream fans in North Bekasi). The sample for this research is NCT Dream fans in North Bekasi who have the decision to purchase TosTos. The sample was carried out using a probability sampling method, namely random sampling. Data collection was carried out using a questionnaire distributed via Google Form to 170 respondents. The analysis in this research uses Multiple Linear Regression Analysis, with t-test hypothesis testing. The results of this research show that in the partial t test packaged gifts have a significant positive effect on purchasing decisions, product quality has a significant positive effect on purchasing decisions, but product distribution does not have a significant effect on purchasing decisions. The results of the f test show that the variables of gift packaging, product quality and product distribution simultaneously have a significant influence on TosTos purchasing decisions (case study of NCT Dream fans in North Bekasi).